The role of behavioral inhibition and parenting for an unfavorable emotional trauma response and PTSD. (21st July 2014) - Asselmann, E.; Wittchen, H.‐U.; Lieb, R.; Höfler, M.; Beesdo‐Baum, K.
<x xml:space="preserve">Abstract</x> Objective The role of behavioral inhibition (BI) and parenting for an unfavorable emotional trauma response (DSM‐IV criterion A2) and post‐traumatic stress disorder (PTSD) development is unclear. Method A community sample of adolescents and young adults (aged 14–24) was followed up over 10 years (N = 2378). Traumatic events, criterion A2, and PTSD (according to DSM‐IV‐TR) were assessed using the M‐CIDI. BI and parenting were assessed using the Retrospective Self‐Report of Inhibition and the Questionnaire of Recalled Parenting Rearing Behavior. Multiple logistic regressions adjusted for sex, age, and number of traumata were used to examine associations of BI as well as maternal and paternal overprotection, rejection, and reduced emotional warmth with (i) criterion A2 in those with trauma (N = 1794) and (ii) subsequent PTSD in those with criterion A2 (N = 1160). Results Behavioral inhibition (BI; odds ratio, OR = 1.32) and paternal overprotection (OR = 1.27) predicted criterion A2 in those with trauma, while only BI (OR = 1.53) predicted subsequent PTSD. BI and paternal emotional warmth interacted on subsequent PTSD (OR = 1.32), that is, BI only predicted PTSD in those with low paternal emotional warmth. Conclusion Our findings suggest that BI and adverse parenting increase the risk of an unfavorable emotional trauma response and subsequent PTSD. Paternal emotional warmth buffers the association between BI and PTSD development.